2018
DOI: 10.1111/jfb.13736
|View full text |Cite
|
Sign up to set email alerts
|

Observations of follicle cell processes in a holocephalan

Abstract: The presence of follicular cellular processes (FCP) that cross the zona pellucida, has been recorded in the ovarian follicles of Callorhinchus callorhynchus. This constitutes the first report describing the presence of these structures in a species of the Holocephali. Considering that FCPs have only previously been reported in the Selachii, these findings suggest that FCPs could have been lost by the Batoidea after their divergence, around 280 M B.P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This is the first time FCP have been found in the family Chimaeridae and the second report of FCP in Order Chimaeriformes overall. The presence of FCP in both Callorhinchus callorhynchus (Díaz Andrade et al ., 2018) and H. colliei suggests that FCP are present throughout the order. The fact that FCP also have been found in the Atlantic sharpnose shark; dusky smooth‐hound; spinner shark, Carcharhinus brevipinna (Mϋller & Henle, 1839); sandbar shark, Carcharhinus plumbeus (Nardo, 1827); and one species of Squaliformes Little gulper shark, but are absent in the batoids – the little skate Leucoraja erinacea (Mitchill, 1825) (Rajiformes); the yellow stingray Urolophus jamaicensis (Cuvier, 1816) (Myliobatiformes); and the marbled electric ray, Torpedo marmorata (Risso, 1810) (Torpediniformes) – suggests that FCP first evolved in the common ancestor to all extant chondrichthyan fishes, but were secondarily lost in superorder Batoidea (Davenport et al ., 2011; Dunbar et al ., 2017; Hamlett et al ., 1999; Prisco et al ., 2002).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is the first time FCP have been found in the family Chimaeridae and the second report of FCP in Order Chimaeriformes overall. The presence of FCP in both Callorhinchus callorhynchus (Díaz Andrade et al ., 2018) and H. colliei suggests that FCP are present throughout the order. The fact that FCP also have been found in the Atlantic sharpnose shark; dusky smooth‐hound; spinner shark, Carcharhinus brevipinna (Mϋller & Henle, 1839); sandbar shark, Carcharhinus plumbeus (Nardo, 1827); and one species of Squaliformes Little gulper shark, but are absent in the batoids – the little skate Leucoraja erinacea (Mitchill, 1825) (Rajiformes); the yellow stingray Urolophus jamaicensis (Cuvier, 1816) (Myliobatiformes); and the marbled electric ray, Torpedo marmorata (Risso, 1810) (Torpediniformes) – suggests that FCP first evolved in the common ancestor to all extant chondrichthyan fishes, but were secondarily lost in superorder Batoidea (Davenport et al ., 2011; Dunbar et al ., 2017; Hamlett et al ., 1999; Prisco et al ., 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Results of the present study and those of Díaz Andrade et al . (2018) suggest that FCP evolved at the base of the chondrichthyan tree, prior to the split between Holocephali and Elasmobranchii. It is suggested that the FCP evolved from microvilli, as both have similar cytoskeletal architecture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation